An Unusual Presentation Of A Spinal Hydatid Cyst – An Operative Surprise - Punia, Prashant; Rege, Ishant; Chugh, Ashish; Gotecha, Sarang (Journal of Neonatal Surgery, 2025)
Isolated primary spinal hydatid disease without any visceral involvement is a rare finding. A middle aged male presented to our institute with a history of localized swelling over the back since 7 years and difficulty in walking since 3 months. On examination, there was a 20x15cm diffuse swelling visible over the back. MRI scan was suggestive of a plexiform neurofibroma, hence surgical excision was planned. After doing a D11 to L2 level hemi-laminectomy , the lesion was dissected in the muscular plane and into the foraminal part. While performing internal debulking , the lesion was incised which then revealed a bunch of pearly white cysts within, much to our surprise. Once these cysts were identified, utmost care was taken to avoid rupture of cysts. On follow up after 3 months, patient was symptom free, ambulatory without support and the MRI showed no remnant or residual of the hydatid disease.